Diversity and Inclusion and Team Performance of Oil and Gas Firms in Rivers State, Nigeria - Oruebo, Stella Daso; David-Alonge, Bosede Olugbenga (ABUAD Journal of Social and Management Sciences, 2024)
The study investigates the relationship between diversity and inclusion and team performance of the oil and gas firms in Rivers State. A survey study was carried out in this study. The population comprised 4520 employees of the oil and gas firms in Rivers State and the samples were 317 employees of the oil and gas firms. The Taro Yamane 1967 formula was used to derive the sample size. The spearman rank order correlation coefficient was used in analysing the stated hypotheses. The findings revealed a positive correlation between the dimensions of diversity and inclusion (diversity training and inclusivity of voices and perspectives) and team performance. The study concludes that diversity and inclusion relate with the team performance of the oil and gas firms. The study recommends enhancing diversity training and inclusivity of voices and perspectives for improved team performance.